Novel Antimicrobial Agents Based on Zinc-Doped Hydroxyapatite Loaded with Tetracycline - Simona Liliana Iconaru; Daniela Predoi; Carmen Steluta Ciobanu; Catalin Constantin Negrila; Roxana Trusca; Steinar Raaen; Krzysztof Rokosz; Liliana Ghegoiu; Monica Luminita Badea; Carmen Cimpeanu (MDPI AG, 2024)
In this paper, we present for the first time the development of zinc-doped hydroxyapatite enriched with tetracycline (ZnHApTe) powders and provide a comprehensive evaluation of their physico-chemical and biological properties. Various techniques such as X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), and Fourier transform infrared spectroscopy (FTIR) were used for the sample's complex evaluation. Moreover, the biocompatibility of zinc-doped hydroxyapatite (ZnHAp) and ZnHApTe nanoparticles was evaluated with the aid of human fetal osteoblastic cells (hFOB 1.19 cell line). The results of the biological assays suggested that these nanoparticles hold great promise as potential candidates for the future development of novel biocompatible and antimicrobial agents for biomedical applications. The antimicrobial properties of the ZnHAp and ZnHApTe nanoparticles were assessed using the standard reference microbial strains Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, and Candida albicans ATCC 10231. The results of the in vitro antimicrobial assay demonstrated that both tested materials exhibited good antimicrobial activity. Additionally, these data also indicated that the antimicrobial effects of the ZnHAp nanoparticles were intensified by the presence of tetracycline (Te). Furthermore, the results also suggested that the antimicrobial activity of the samples increased with the incubation time.